Effect of high temperature cooking on the quality of rice porridge - Chen, Cunshe; Jiang, Siyuan; Li, Mengfei; Li, You; Li, He; Zhao, Fen; Pang, Zhihua; Liu, Xinqi (International Journal of Agricultural and Biological Engineering, 2021)
In order to explore the effect of high-temperature cooking instant porridge on the taste and quality of porridge, this study explored the changes in the taste quality of rice porridge under different heating times (15 min, 20 min, 25 min and 30 min) at a higher initial temperature (100°C), and compared with that cooked at room temperature (25°C), and explained the reasons for the change. From the perspective of migration rate in moisture content, the rice porridge with special treatment has a more rapid moisture change, which makes texture, whiteness, smell and other factors change in a shorter time and increases the taste quality. It was concluded that under special treatment condition of starting with 100°C water and heating for 15 min, the kinds of rice flavor increased 2.2 times, the white of rice decreased by 10.04%, hardness decreased by 3.54 times, and the elasticity decreased by 35.48% respectively. In general, cooking with higher initial temperature (100°C) is more valuable than cooking from 25°C, in terms of the texture, flavor, saving time, and stable quality during the household and industrial production of instant porridge. Keywords: rice porridge, low frequency NMR, sensory evaluation, GC-MS, confocal laser scanning microscope DOI: 10.25165/j.ijabe.20211405.6412 Citation: Chen C S, Jiang S Y, Li M F, Li Y, Li H, Zhao F, et al. Effect of high temperature cooking on the quality of rice porridge. Int J Agric & Biol Eng, 2021; 14(5): 247–254.